Evaluation of human umbilical vein endothelial cells growth onto heparin-modified electrospun vascular grafts - Caracciolo, Pablo Christian (2021)
One of the main challenges of cardiovascular tissue engineering is the development of bioresorbable and compliant small-diameter vascular grafts (SDVG) for patients where autologous grafts are not an option. In this work, electrospun bilayered bioresorbable SDVG based on blends of poly(L-lactic acid) (PLLA) and segmented polyurethane (PHD) were prepared and evaluated. The inner layer of these SDVG was surface-modified with heparin, following a methodology involving PHD urethane functional groups. Heparin was selected as anticoagulant agent, and also due to its ability to promote human umbilical vein endothelial cells (HUVECs) growth and to inhibit smooth muscle cells over-proliferation, main cause of neointimal hyperplasia and restenosis. Immobilized heparin was quantified and changes in SDVG microstructure were investigated through SEM. Tensile properties of the heparin-functionalized SDVG resembled those of saphenous vein. Vascular grafts were seeded with HUVECs and cultured on a flow-perfusion bioreactor to analyze the effect of heparin on graft endothelization under simulated physiological-like conditions. The analysis of endothelial cells attachment and gene expression (Real-Time PCR) pointed out that the surface functionalization with heparin successfully promoted a stable and functional endothelial cell layer.